2017
DOI: 10.1007/s10916-017-0810-8
|View full text |Cite
|
Sign up to set email alerts
|

Can a Novel ICU Data Display Positively Affect Patient Outcomes and Save Lives?

Abstract: The aim of this study was to quantify the impact of ProCCESs AWARE, Ambient Clinical Analytics, Rochester, MN, a novel acute care electronic medical record interface, on a range of care process and patient health outcome metrics in intensive care units (ICUs). ProCCESs AWARE is a novel acute care EMR interface that contains built-in tools for error prevention, practice surveillance, decision support and reporting. We compared outcomes before and after AWARE implementation using a prospective cohort and a histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 18 publications
0
36
0
Order By: Relevance
“…Notably, five more studies [45][46][47][48][49] meet most of our inclusion criteria but were excluded due to various, although little, deviations. Three studies [45][46][47] report cost-savings after a bundle of information technology was implemented simultaneously, but the economic benefit could not solely be attributed to the EHR based CDS intervention. The fourth publication is an NHS health technology assessment (HTA) report [48].…”
Section: Additional Studies Worth Mentioningmentioning
confidence: 99%
“…Notably, five more studies [45][46][47][48][49] meet most of our inclusion criteria but were excluded due to various, although little, deviations. Three studies [45][46][47] report cost-savings after a bundle of information technology was implemented simultaneously, but the economic benefit could not solely be attributed to the EHR based CDS intervention. The fourth publication is an NHS health technology assessment (HTA) report [48].…”
Section: Additional Studies Worth Mentioningmentioning
confidence: 99%
“…Only one study reported the net monetary bene t (NMB) of the intervention in relation to a prede ned threshold. [5,42] Additional Studies Worth Mentioning Notably, ve more studies [43][44][45][46][47] meet most of our inclusion criteria, but were excluded due to various, although little, deviations. Three studies [43][44][45] report cost-savings after a bundle of information technology was implemented simultaneously, but the economic bene t could not solely be attributed to the EHR based CDS intervention.…”
Section: Lack Of Considering All Cost Componentsmentioning
confidence: 99%
“…Only one study reports on the net monetary bene t (NMB) of the intervention in relation to a prede ned threshold. [5,44] Additional studies worth mentioning Notably, ve more studies [45][46][47][48][49] meet most of our inclusion criteria but were excluded due to various, although little, deviations. Three studies [45][46][47] report cost-savings after a bundle of information technology was implemented simultaneously, but the economic bene t could not solely be attributed to the EHR based CDS intervention.…”
Section: Economic Impact For Prevalent Application Areasmentioning
confidence: 99%